Development, internal consistency, reliability and validity of a scale of occupational hazards in Spanish. - Boada-Grau, Joan; Robert-Sentís, Lluís; Gil-Ripoll, Carme; Vigil-Colet, Andreu (Anales de Psicología / Annals of Psychology, 2013)
In this article, we study the psychometric properties of a short scale (RL-14) created in order to ascertain the information / training received by employees and their psychophysiological disorders. The participants of this study were 1.489 employees in various sectors including education, construction, transport, health, industry, trade and hospitality. The results of an exploratory and confirmatory factor analysis show a structure consisting of two factors: "(F1)Information and Training" and "(F2) Psychophysiological Pathologies". In addition, the two factors obtained have adequate reliability and present evidence of the validity of the two factors if some sociodemographic variables, such as fatigue, burnout and job strain are taken as benchmarks. In short, this scale may be suitable for the proper identification of workplace hazards. Future research could use the RL-14 as a tool for screening in combination with other instruments.